PLATFORMIZED RELIGIOUS AUTHORITY: Rethinking Legitimacy in the Age of Social Media Influencers - Sulfikar, Achmad; Yasmine, Daisy Indira (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2025)
The proliferation of social media has fundamentally reshaped the landscape of religious authority in Muslim societies, shifting the locus of legitimacy from traditional ulama and institutions to a new class of digital actors known as “religious influencers.” While existing scholarship, grounded in Weberian typology or early digital religion theories, has extensively documented the fragmentation of authority, these frameworks remain insufficient to fully account for the emergence of authority structures shaped by algorithmic logics. This article addresses this theoretical gap by critically reviewing the literature and proposing a novel conceptual framework, “Platformized Religious Authority.” We argue that contemporary religious authority is not monolithic but a hybrid negotiation of three intersecting dimensions: knowledge-based authority (traditional scholarship), charisma-based authority (performative piety), and platform-based authority (algorithmic visibility and engagement metrics). In Indonesia, this framework reveals how platform logic acts as a new gatekeeper, favoring content that is visually performative and affectively resonant, thereby commodifying theology and forming algorithmic enclaves. By integrating the perspective of platform studies from communication science into the sociology of religion, this study offers a more robust model for understanding how religious legitimacy is produced, maintained, and contested in the attention economy.